Effect of Oxymetholone on The Sperm Quality and Sex Hormone Profile in Male Rats - Zahraa Lateef Abd; Bushra Abbas alzubaidi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The objective of present study was to evaluated the effect of Oxymetholone drug on sperm parametersand sex hormone in adult male rats. Twenty male rats sexually mature were randomly divided into twogroups; Each group has 10 rats. The treated group administered orally with Oxymethololne drug 5 mg/gbody weight/ day of for 60 days while the control group administered orally normal saline per day. SPSSanalysis of data generated with P< 0.05 considered statistically significant. The results showed a significantdecrease (p <0.05) in the mean sperm count, the motility and viability in treated group compared to control.Also, LH (luteinizing hormone) FSH (follicle stimulating hormone) and T (testosterone) of the treated groupwere significantly lowered compared to the control. The administration of Oxymethylene induces low spermquality with reduction in sex hormone.